Penyuluhan Kesehatan Meningkatkan Pengetahuan Tentang Manfaat Prenatal Gentle Yoga Pada Ibu Hamil - Nurhidayah; Risnah, Risnah (Universitas Mulawarman, 2022)
Prenatal gentle yoga is one type of modification of hatha yoga that is adapted to the condition of pregnant women. Yoga is a movement of the body with the harmonization of mind and soul. One of the yoga exercises intended for pregnant women is the Pranayama Position. Regular yoga practice during pregnancy can increase fetal weight and reduce preterm birth and childbirth complications. This community service aims to increase the knowledge of pregnant women about the benefits of prenatal gentle yoga. Existing problems are solved through community outreach activities through three stages, namely preparation, implementation and evaluation. The preparatory stage involves taking initial data and coordinating with the Puskesmas to plan the process of implementing counseling with a theme according to the needs of pregnant women, then the implementation stage begins with and introduces yourself, explains the aims and objectives of the counseling and distributes questionnaires to measure the knowledge of pregnant women before being given counseling. The evaluation phase consisted of discussion and question and answer as well as distributing questionnaires after health education. This activity was carried out on June 2, 2022 at the Bajeng Health Center which was attended by 21 pregnant women. The conclusion is that there are differences in knowledge before and after giving health education about the benefits of prenatal gentle yoga.